2021
DOI: 10.1093/mnras/stab1798
|View full text |Cite
|
Sign up to set email alerts
|

The Deeper, Wider, Faster programme: exploring stellar flare activity with deep, fast cadenced DECam imaging via machine learning

Abstract: We present our 500 pc distance-limited study of stellar flares using the Dark Energy Camera as part of the Deeper, Wider, Faster Program. The data was collected via continuous 20-second cadence g band imaging and we identify 19,914 sources with precise distances from Gaia DR2 within twelve, ∼3 square-degree, fields over a range of Galactic latitudes. An average of ∼74 minutes is spent on each field per visit. All light curves were accessed through a novel unsupervised machine learning technique designed for an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 85 publications
2
10
0
Order By: Relevance
“…The longest duration Kepler longcadence flare lasts 260 minutes, and the shortest GALEX flare detected spans only 30 s. The short-cadence Kepler flares noted in Namekata et al (2017) and displayed in Figure 15 span the range of durations between these two extremes. We note that a similar plot of flare duration versus energy for the shortduration optical flares in the Webb et al (2021) sample (their Figure 8) shows a similar behavior as the Kepler short-cadence flare characteristics. This evidence supports a continuum of flare durations between a few tens of seconds all the way up to several hours.…”
Section: Short Timescale Flaressupporting
confidence: 59%
See 4 more Smart Citations
“…The longest duration Kepler longcadence flare lasts 260 minutes, and the shortest GALEX flare detected spans only 30 s. The short-cadence Kepler flares noted in Namekata et al (2017) and displayed in Figure 15 span the range of durations between these two extremes. We note that a similar plot of flare duration versus energy for the shortduration optical flares in the Webb et al (2021) sample (their Figure 8) shows a similar behavior as the Kepler short-cadence flare characteristics. This evidence supports a continuum of flare durations between a few tens of seconds all the way up to several hours.…”
Section: Short Timescale Flaressupporting
confidence: 59%
“…The motivating paper for the current study, Brasseur et al (2019), examined a population of short-duration flares in the NUV using GALEX data at 10 s cadence. Webb et al (2021) used 20 s cadenced optical imaging to study stellar flares within 500 pc across 12 fields of observations with the Dark Energy Camera, and found that the majority of flares occur on timescales less than 8 minutes, with a range of optical flare enhancements ranging from 0.1-1.8 mag. Howard & MacGregor (2021) reported on flare light-curve profiles seen in the TESS bandpass at 20 s cadence, finding that roughly half of the large flares studied exhibited substructure in the rise phase of the flares.…”
Section: Short Timescale Flaresmentioning
confidence: 99%
See 3 more Smart Citations